ANALYSIS OF THE EFFECT OF WORK MOTIVATION AND WORK ENVIRONMENT ON TEACHER JOB SATISFACTION AT SMAN 19 SURABAYA - Baharudin Amin, Muhammad Arya; Adiwaty, Mei Retno (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This ponder points to decide the impact of work inspiration and work environment on the work fulfillment of instructors at SMAN 19 Surabaya. This think about employments a quantitative approach with essential information collected through survey procedures with a Likert scale on a test of 58 respondents. In expansion to the essential information, auxiliary information were too gotten, to be specific information given by the company. The information gotten was at that point analyzed utilizing Halfway Slightest Square (PLS) and the comes about appeared that by and large work fulfillment is impacted by work inspiration and work environment factors and the rest by other factors exterior the investigate show. The comes about appeared that work inspiration contains a positive and critical effect on work fulfillment, and the work environment incorporates a positive and noteworthy impact on the work fulfillment of instructors at SMAN 19 Surabaya. Keywords: Work Motivation; Work Environment; Job Satisfaction